The association between retinal vein ophthalmodynamometric force change and optic disc excavation. Issue 5 (19th December 2008) - Morgan, W H; Hazelton, M L; Balaratnasingamm, C; Chan, H; House, P H; Barry, C J; Cringle, S J; Yu, D-Y
Abstract : Aim: Retinal vein ophthalmodynamometric force (ODF) is predictive of future optic disc excavation in glaucoma, but it is not known if variation in ODF affects prognosis. We aimed to assess whether a change in ODF provides additional prognostic information. Methods: 135 eyes of 75 patients with glaucoma or being glaucoma suspects had intraocular pressure (IOP), visual fields, stereo optic disc photography and ODF measured on an initial visit and a subsequent visit at mean 82 (SD 7.3) months later. Corneal thickness and blood pressure were recorded on the latter visit. When venous pulsation was spontaneous, the ODF was recorded as 0 g. Change in ODF was calculated. Flicker stereochronoscopy was used to determine the occurrence of optic disc excavation, which was modelled against the measured variables using multiple mixed effects logistic regression. Results: Change in ODF (p = 0.046) was associated with increased excavation. Average IOP (p = 0.66) and other variables were not associated. Odds ratio for increased optic disc excavation of 1.045 per gram ODF change (95% CI 1.001 to 1.090) was calculated. Conclusion: Change in retinal vein ODF may provide additional information to assist with glaucoma prognostication and implies a significant relationship between venous change and glaucoma patho-physiology.